Personalized Dietary Recommendations Based on Lipid-Related Genetic Variants: A Systematic Review - Pérez-Beltrán, Yolanda E.; Rivera-Iñiguez, Ingrid; Gonzalez-Becerra, Karina; Pérez-Naitoh, Naomi; Tovar, Juscelino; Sáyago-Ayerdi, Sonia G.; Mendivil, Edgar J. (Frontiers in Nutrition, 2022)
Background Obesity and dyslipidemias are risk factors for developing cardiovascular diseases, the leading causes of morbidity and mortality worldwide. The pathogenesis of these diseases involves environmental factors, such as nutrition, but other aspects like genetic polymorphisms confer susceptibility to developing obesity and dyslipidemias. In this sense, nutrigenetics is being used to study the influence of genetic variations on the circulating lipid responses promoted by certain nutrients or foods to provide specific dietary strategies considering the genetic factors in personalized nutrition interventions. Objective To identify throughout a systematic review the potential nutrigenetic recommendations that demonstrate a strong interaction between gene-diet and circulating lipid variations. Methods This systematic review used the PRISMA-Protocol for manuscript research and preparation using PubMed and ScienceDirect databases. Human studies published in English from January 2010 to December 2020 were included. The main results were outcomes related to gene-diet interactions and plasmatic lipids variation. Results About 1,110 articles were identified, but only 38 were considered to fulfill the inclusion criteria established based on the reported data. The acquired information was organized based on gene-diet interaction with nutrients and components of the diet and dietary recommendation generated by each interaction: gene-diet interaction with dietary fats, carbohydrates or dietary fiber, gene-diet interaction with nutraceutical or dietary supplementation, and gene-diet interaction with proteins. Conclusion Findings included in this systematic review indicated that a certain percentage of dietary macronutrients, the consumption of specific amounts of polyunsaturated or monounsaturated fatty acids, as well as the ingestion of nutraceuticals or dietary supplements could be considered as potential strategies for the development of a wide range of nutrigenetic interventions since they have a direct impact on the blood levels of lipids. In this way, specific recommendations were identified as potential tools in developing precision diets and highlighted the importance of personalized nutrition. These recommendations may serve as a possible strategy to implement as dietary tools for the preventive treatment and control alterations in lipid metabolism. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021248816, identifier [CRD42021248816].